Pleomorphic Fibroma of Tendon Sheath in Palmar Area - Mehmet Dadacı; Bilsev İnce; Fatma Bilgen; Zeynep Altuntaş; Tuba Sodalı; Ozan Bitik (Turkish Journal of Plastic Surgery, 2016)
Tendon sheath fibromas are slowly growing, firm, immobile, and painless masses that are frequently seen in fingers. They are commonly observed in middle-aged males. In our report, we discuss a case of a painless mass in the palmar area that was diagnosed as a pleomorphic fibroma of tendon sheath on histopathologic examination in light of the literature.